The Relationship between Glycemic Index, Social Support and Sleep Quality in Patients with Type 2 Diabetes - Mohammadreza Mirzaei; Mohammad Hossein Sharifi; Sepideh Mahboobi; Hossein Shahinfar; Mina Karimi; Mohammad Hassan Eftekhari (International Journal of Nutrition Sciences, 2025)
Background: Social support and sleep quality can be beneficial in both self-care behaviors and health outcomes in subjects with type 2 diabetes (T2DM). The aim of this study was to analyze the relationship between glycemic index, social support and sleep quality in patients with T2DM.Methods: In a cross-sectional study, 156 men and 144 women with T2DM were enrolled from July to September 2020. Level of self-care activities, social support, and sleep quality were measured with validated and appropriate questionnaires, and clinical characteristics were acquired from patients’ medical records.Results: The mean age of the participants was 50.83±7.14 years. According to this study, more than 60% of participants had poor selfcare behaviors (37.68±12.94) and poor sleep quality (7.55±3.80) and the overall average of the social support score was moderate (67.73±19.85). A significant negative association was noticed between HbA1c and selfcareactivities and social support score (r=-0.346, p<0.001 and r=-0.309, p<0.001, respectively). There was a significant positive relationship between HbA1c and Pittsburgh Sleep Quality Index (PSQI) score (r=0.469, p<0.001). Also, a significant negative association was observed between social support and PSQI score (r=-0.393, p<0.001).Conclusion: Glycemic control, self-care behaviors, high social support, and optimal sleep quality are suggested to be considered in diabetes management guidelines and policy making.